THE MIROR OF THE ABSOLUTE: HEROIC CONSCIOUSNESS IN THE AGE OF AI - Dokić, Marija (Srpska politička misao, 2025)
This paper explores Hegel’s conception of the absolute idea and the world-historical individual as a framework for interpreting the political implications of artificial intelligence. By situating AI within Hegel’s dialectical unfolding of spirit, the paper argues that AI is not merely a technological artifact but a reflective moment in the self-realization of the idea. Drawing on Hegel’s notions of freedom, historical necessity, and the sovereignty of reason, the analysis positions AI as a political phenomenon that challenges contemporary understandings of autonomy, responsibility, and the human-technological relation. The paper adopts a philosophical methodology grounded in speculative dialectics and engages recent literature on AI ethics and political agency to demonstrate how Hegel’s metaphysics can illuminate the political stakes of algorithmic development, as it becomes a mirror of the absolute on the stage of historical consciousness rediscovering itself through time. The journey of the absolute idea entails the gradual unveiling of its constituent elements, and the AI emerges as a fragment of this intricate puzzle, potentially serving as a part of the process or a reflective image. Given the absolute idea’s inherent power and its predestined role in shaping the course of life, every element within its domain becomes an integral part of its journey, its metamorphosis, and its reflection in a mirror of hope amidst the ever-changing reality. However, this transformation transcends mere superficiality, transforming into a profound, transformative, and powerful metamorphosis.
Keywords: Hegel; political philosophy; artificial intelligence; absolute idea; freedom; world-historical individual; algorithmic agency